Primary Sjögren’s syndrome presenting with non-diffuse membranoproliferative glomerulonephritis-like lesions in cryoglobulinemic glomerulonephritis: a case report - Duan, Zhi-Yu; Cai, Guang-Yan; Chen, FengKun; Tang, XuanLi; Zhang, Xu; Ren, YaLi; Song, Yan (Frontiers in Immunology, 2025)
BackgroundIn primary membranoproliferative glomerulonephritis (MPGN), mesangial and capillary proliferation manifests as a diffuse, spherical change; in secondary MPGN, lesions are predominantly focal and segmental.Case presentationA 52-year-old woman with a 2-year history of primary Sjögren’s Syndrome (pSS) and no prior renal involvement developed fever, nephrotic syndrome, and acute kidney injury with oliguria after a pulmonary infection. Her highest recorded serum creatinine level was 327.3 µmol/L, and the lowest serum albumin level was 22.1 g/L. Laboratory findings included an antinuclear antibody titer of 1:320, anti-SSA/52KD antibody positivity, complement C3 of 0.468 g/L, complement C4 of 0.0107 g/L, and rheumatoid factor (RF) 678 IU/mL. The highest 24-hour urinary protein quantification reached 9.78 g/24h. After anti-infective treatment, urine output gradually increased, and edema resolved. Cryoglobulin testing showed type II cryoglobulin positivity. Light microscopy revealed MPGN-like lesions in 66.7% of glomeruli and mesangial proliferative glomerulonephritis-like lesions in 25%. Final diagnosis was MPGN. Cyclophosphamide and methylprednisolone were administered. After 30 months follow-up, the patient’s serum creatinine level was 82.1 µmol/L; proteinuria was negative.ConclusionThis case represents the first reported instance of non-diffuse MPGN with cryoglobulinemic GN secondary to pSS. Infection may serve as a key factor in exacerbating cryoglobulinemia and triggering cryoglobulinemic GN onset.